A dream of lies: stories of Bangladeshi maid migrants in the Middle East - Mustari, Sohela; Hossain, Md. Shamim; Hamide, Md.Shamim (Taylor & Francis, 2024)
Being a socially conservative country, a number of Bangladeshi female migrant workers working in abroad are not as many as the male. However, in recent times, the number increased a lot, but still female migrant workers are very much under-researched and a minor in getting policy attention. This present study thus tries to fill that gap and to identify the influencing factors of female maid migration, their life as migrants and the reintegration processes of these migrant returnees. This is a qualitative study where interviews were conducted 20 female who worked in middle east as the housemaid and who were registered as migrant returnees at different government and nongovernment organizations. A thematic analytical procedure was used to analyse the data. The study finds that female workers migrate to Middle East mostly for economic purposes to overcome their economic challenges in home country; however, they face a number of violences such as physical abuse, socio-psychological torture which put their dream in challenge. The result of the study also shows that as the returnees, these female workers faced reintegration challenges too. To make their dream come true, with many other policies, government should introduce functional monitoring cells in the respective countries.